Stuck in a marriage: Labor market shocks, divorce and intra-household reallocation - Wataru Kureishi; Hannah Paule-Paludkiewicz; Hitoshi Tsujiyama; Midori Wakabayashi (Deutsche Bundesbank, 2025)
Families play an important role in providing insurance against adverse shocks, but little is known about how shocks affect the family structure itself. We study the impact of a labor market shock on divorce and intra-household allocation of resources, exploiting a naturalexperimental earthquake shock and large-scale panel data. We provide novel evidence that the earthquake reduces the probability of divorce, especially for dual-earner couples. We show that the key driver is the gender-specific labor market shock associated with the earthquake, with female workers experiencing much worse labor market conditions than male workers after the earthquake. The probability of divorce declines because the value of divorce for wives decreases due to the labor market shock, while the value of marriage remains high because of the family insurance provided by the husband to compensate for the wife's loss of income. We show that these results are consistent with a collective household model with limited commitment, and further derive a novel theoretical prediction for the intra-household reallocation of household resources from the wife to the husband. We provide direct evidence for this prediction, using unique panel data with comprehensive information on personal consumption and time use within households.
Keywords: D13; J12; J16; J22; 330; Marital dissolution; intra-household allocation; family insurance; earthquake; gender-specific labor market shock